(untitled) (Intercom - Brazilian Journal of Communication Sciences, 2026)
The study analyzes the discursive contradictions in the responses of the ChatGPT and Gemini language models on the environmental impact of artificial intelligence (AI). Based on a thematic analysis, responses generated in “interviews” with semi-structured prompts about the relationship between AI and the global climate crisis were examined. Three themes were identified: corporatism, belief in the potential of technology, and shared responsibility. It is concluded that algorithmic textualities act to maintain socio-technical imaginaries that shift environmental responsibilities, contributing to the naturalization of the ecological impacts of AI. Finally, the urgency of the debate on eco-media literacy in the field of Communication is emphasized.